2021
DOI: 10.1088/1755-1315/713/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

The chemical changes in the total antioxidant status and biological activity of GSTP1 polymorphism on nasopharyngeal carcinoma patients

Abstract: Oxidative stress is associated with cancer, including NPC, which is developed by the relation of genetic alteration, EBV infection, and environmental risk. Ile/Val genotype of GSTP1 polymorphism decrease enzyme functions and result in lower total antioxidant status. This study aimed to identify the association of GSTP1 polymorphism and the TAS level. This was a cross-sectional design study. There were 29 NPC patients with their blood as the samples of the study. Blood as the samples for identifying GSTP1 polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several populations in the world showed that GSTM1 gene null polymorphism and/or GSTT1 had the risk of type 2 DM (T2DM) compared with healthy control group [14], [15]. GSTT1 dan GSTM1 gene polymorphism and some diseases have been studied in Indonesia [16], [17], [18], [19], however, so far not research on T2DM. Therefore, this study was aimed to determine the role of GSTM1 and GSTT1 gene polymorphism in T2DM at Universitas Sumatera Utara Hospital, Medan, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Several populations in the world showed that GSTM1 gene null polymorphism and/or GSTT1 had the risk of type 2 DM (T2DM) compared with healthy control group [14], [15]. GSTT1 dan GSTM1 gene polymorphism and some diseases have been studied in Indonesia [16], [17], [18], [19], however, so far not research on T2DM. Therefore, this study was aimed to determine the role of GSTM1 and GSTT1 gene polymorphism in T2DM at Universitas Sumatera Utara Hospital, Medan, Indonesia.…”
Section: Introductionmentioning
confidence: 99%